A new dawn for energy storage: An interdisciplinary legal and techno-economic analysis of the new EU legal framework. (December 2022) - Parra, David; Mauger, Romain
Abstract: Beyond the hitherto high cost of storage technologies, regulatory and market barriers such as lack of definition, double grid charges and unclear ownership rules have hindered their deployment. These barriers, however, have been largely overlooked in energy modelling research, calling for new interdisciplinary research. In 2019, the new EU electricity market directive was released with energy storage as a central element. Against this background, we study the impact of the new EU legal framework on the value of energy storage across 12 countries using techno-economic modelling informed by legal analysis and expert interviews. We conclude that the new legal regime fits for behind-the-meter batteries which could become widespread across Europe, considering their important value creation. This could also be the case for community storage, especially if national transpositions of the new legal regime prevent double grid charges or at least, moderate them. Legal certainty is created by prohibiting network operators to operate energy storage, but we argue that benefit stacking including applications which support electricity grids would only be possible if network operators set up transparent flexibility markets for the interested parties. Highlights: Analysis of impact of the new EU legal framework on the value of energy storage. Interdisciplinary methodology using legal analysis, expert interviews and modelling. Study of various storage technologies and applications across 12 EU countries. New legal regime fits for behind-the-meter batteries, which can become widespread. Role of community storage will depend on grid charges which will apply nationally.